a)2x + 3= 7 b) 2x + 7 chia hết cho x + 1

a)2x + 3= 7

b) 2x + 7 chia hết cho x + 1

2 bình luận về “a)2x + 3= 7 b) 2x + 7 chia hết cho x + 1”

  1. a, 2x + 3 =7
    => 2x =7-3
    => 2x=4
    => x=2
    vậy x=2
    b,  (2x+7) $\vdots$(x+1)
    =>(2x+2+5) $\vdots$ (x+1)
    => 5 $\vdots$ (x+1)
    => (x+1) $\in$ Ư (5) = { 1 , -1 , 5 , -5}
    ta có bảng 
    x+1                   1                   -1                      5                  -5
    x                       0                    -2                     4                  -6
    ĐK                  TM                  TM                   TM                TM
     Vậy n $\in$  { 0 , -2 , 4 ,-6}

    Trả lời
  2. Giải đáp:
    a ) x = 2 ; b) x= 4 
    Lời giải và giải thích chi tiết:
    a ) 2x + 3 = 7 
    ⇒ 2x = 7 – 3 
    2x = 4 
    x = 4 : 2
    x = 2 
    vậy x = 2 
    b ) 2x + 7 chia hết  cho x+ 1 
    ta có  2x + 7 : x + 1 
    mà : x + 1 : x + 1 ⇒ 2 ( X +1 ) : x +1 ⇒2x + 2 😡 + 1 
    ⇒ ( 2x + 7 ) – ( 2x + 2 ) : x + 1 ⇒2x + 2 : x + 1 
    ⇒ 5 : x + 1 ⇒ x + 1 ∈ Ư ( 5 ) 
    Mà:  Ư (5)+{1;5} ; x + 1> 1 ⇒ x + 1 = 5
    ⇒ x = 5 -1 =4 
    x = 4 
    Vậy x = 4 

    Trả lời

Viết một bình luận

Câu hỏi mới